Translation problems in advertising: a study of selected South African and German advertising slogans - Schmidt, Petra Monika (My University, 2015)
'This dissertation studies translation problems in advertising on the basis of selected South African and German advertising slogans. A part of the study is also dedicated to the analysis of common linguistic features in advertising slogans and their psychological impact on consumer behaviour. It includes a brief outline of the applicability of translation: theory to the translation of advertising slogans. The problems in translating advertising slogans basically result from the "untranslatability" of certain stylistic-. linguistic features such as plays on words, idioms, proverbs or rhymes. Most of these features are so embedded in a specific culture that they can only be understood by persons belonging to that culture. There is no basic formula for the translation of advertising _ slogans. The translator has to decide whether the slogan should be translated by means of a word for word translation, a paraphrase or imitation in order to be effective and persuasive. Very often, however, the creation of a completely new slogan in the target language is the most effective way of rendering the mood and spirit of the original advertising slogan. The South African and German advertising slogans in this study were selected at random and stem solely from printed media, such as magazines, newspapers and periodicals. The term "South African" slogans refers only to English product advertisements and not to those originally created in Afrikaans or other languages.
A Dissertation Submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg . in Fulfilment of the Requirements for the Degree of Master of Arts in Translation Johannesburg 1982